Digestion procedures for the determination of antimony and arsenic in small amounts of peat samples by hydride generation-atomic absorption spectrometry - Krachler, Michael; Shotyk, William; Emons, Hendrik (Analytica chimica acta, 2001)
Closed-pressurised and open vessel digestion procedures for the mineralisation of small amounts (∼100mg) of peat samples have been developed and evaluated. The two trace elements As and Sb were quantified in the diluted digests by flow injection-hydride generation-atomic absorption spectrometry (FI-HG-AAS). Optimisation of the analytical procedures was carried out with two bulk peat materials one of which was prepared as internal reference material. Both peat specimens were additionally characterised by instrumental neutron activation analysis with respect to their concentrations of As and Sb. Good agreement between instrumental neutron activation analysis (INAA) results and concentrations determined by HG-AAS were obtained. The use of adequate reference materials during the course of all experiments guaranteed precise and accurate results. Various acid mixtures with and without hydrofluoric acid were tested, because preliminary experiments revealed that HF in the digestion mixture leads to the formation of the gaseous AsF5 resulting in diminished recoveries of As when open vessel digestion procedures are employed. Avoiding HF for mineralisation of peat led to low recoveries for Sb because distinct amounts of Sb are associated with silicates. Closed-pressurised vessel digestion proved to be less effective compared to open vessel mineralisation. For successful quantification of both elements, two digestion procedures are needed, one without HF for As and another one with HF to liberate Sb from the silicates. The optimised open vessel digestion procedure was applied to the determination of ancient peat samples dating back to 9300 calendar years before present. Concentrations of both elements showed a broad spread with values ranging from 18 to 1500 and 300 to 5700ngg−1 for Sb and As, respectively.
Gesehen am 06.10.2020